2022
DOI: 10.54393/pbmj.v5i6.190
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Different Types of Urinary Incontinence and Their impact on Quality of Life of Pakistani Women

Abstract: The International Continence Society (ICS) defines Incontinence of urine as involuntary loss of urine. Objective: To determine the frequencies of different types of incontinence of urine and their impact on quality of life of Pakistani women. Method: Descriptive observational study was conducted at outpatient department of five centers. Three validated questionnaires were used for quality-of-life assessment, International Consultation Incontinence Questionnaire Short Form (ICIQ-SF), Medical Outcome Study 36 it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…A study was conducted in Pakistan to determine the frequencies of different types of urinary incontinence and their impact on quality of life in women. It was observed that out of 436 women, 281 had mixed type of urinary incontinence and had a greater impact on life quality [18]. Similar ndings were observed in another recent study published in 2022, where approximately 46% of female married population had some sort of urinary incontinence which impacted their life adversely [19].…”
Section: Discussionsupporting
confidence: 61%
“…A study was conducted in Pakistan to determine the frequencies of different types of urinary incontinence and their impact on quality of life in women. It was observed that out of 436 women, 281 had mixed type of urinary incontinence and had a greater impact on life quality [18]. Similar ndings were observed in another recent study published in 2022, where approximately 46% of female married population had some sort of urinary incontinence which impacted their life adversely [19].…”
Section: Discussionsupporting
confidence: 61%
“…In Punjab (Pakistan), an observational study estimated the prevalence of UI of any type in Pakistani women. They concluded that mixed urinary incontinence (MUI) was most prevalent (64.45%); however, Stress UI and Urge UI came later with 29.59% and 5.96%, respectively 6 .Stress urinary incontinence has distressed various aspects of life, such as relationships, emotional health, sleep, work productivity, depression, and general health-related quality of life (HRQOL) 7 . The International Continence Society (ICS) outlines urinary incontinence (UI) as the patient complains of involuntary seepage or leakage of urine.…”
Section: Introductionmentioning
confidence: 99%